Seawater carbonate chemistry and phytoplankton, copepod development, and fatty acid accumulation - McLaskey, Anna K; Keister, Julie E; Schoo, Katherina L; Olson, M Brady; Love, Brooke A; Zhang, Y (PANGAEA, 2019)
Change in the nutritional quality of phytoplankton is a key mechanism through which ocean acidification can affect the function of marine ecosystems. Copepods play an important role transferring energy from phytoplankton to higher trophic levels, including fatty acids (FA)-essential macronutrients synthesized by primary producers that can limit zooplankton and fisheries production. We investigated the direct effects of pCO2 on phytoplankton and copepods in the laboratory, as well as the trophic transfer of effects of pCO2 on food quality. The marine cryptophyte Rhodomonas salina was cultured at 400, 800, and 1200 μatm pCO2 and fed to adult Acartia hudsonica acclimated to the same pCO2 levels. We examined changes in phytoplankton growth rate, cell size, carbon content, and FA content, and copepod FA content, grazing, respiration, egg production, hatching, and naupliar development. This single-factor experiment was repeated at 12°C and at 17°C. At 17°C, the FA content of R. salina responded non-linearly to elevated pCO2 with the greatest FA content at intermediate levels, which was mirrored in A. hudsonica; however, differences in ingestion rate indicate that copepods accumulated FA less efficiently at elevated pCO2. A. hudsonica nauplii developed faster at elevated pCO2 at 12°C in the absence of strong food quality effects, but not at 17°C when food quality varied among treatments. Our results demonstrate that changes to the nutritional quality of phytoplankton are not directly translated to their grazers, and that studies that include trophic links are key to unraveling how ocean acidification will drive changes in marine food webs.
Keywords: Acartia hudsonica; Animalia; Arthropoda; Behaviour; Biomass/Abundance/Elemental composition; Bottles or small containers/Aquaria (<20 L); Chromista; Cryptophyta; Growth/Morphology; Laboratory experiment; Laboratory strains; Not applicable; Phytoplankton; Reproduction; Rhodomos Sali; Single species; Species interaction; Temperature; Zooplankton